Аnticoronaviral Activity of Triterpenoids - Denisov, M.S.; Beloglazova, Ya.A. (Biomedical Chemistry: Research and Methods, 2020)
The discovery and investigations of new therapeutic agents with anticoronaviral activity is extremely important due to the COVID-19 pandemic caused by the SARS-CoV-2 virus. Currently, there are no anti-COVID-19 drugs, characterized by efficacy which has been proved in correspondence with criteria of evidence-based medicine. However, there are some anti SARS-CoV-2 drugs, acting on the other Coronaviridae family member causing SARS (Severe Acute Respiratory Syndrome) and MERS (Middle East Respiratory Syndrome). Consequently, a wide range of organic substances of synthetic and natural origin were studied for the anticoronaviral activity. The review summarizes and systematizes the literature data on the anti-coronavirus activity of triterpenoids. The structural features of triterpenoids, which are important for the mechanisms of anticoronaviral activity, are discussed. The structures of the most active compounds are presented. The material is classified by approaches to study the anticoronaviral activity of individual substances or plants extracts. Recommendations for the further research of triterpenoids anticoronaviral activity are given.